A superlinear speedup region for matrix multiplication - Gusev, Marjan; Ristov, Sasko (Concurrency and computation, 2014)
SUMMARYThe realization of modern processors is based on a multicore architecture with increasing number of cores per processor. Multicore processors are often designed such that some level of the cache hierarchy is shared among cores. Usually, last level cache is shared among several or all cores (e.g., L3 cache) and each core possesses private low level caches (e.g., L1 and L2 caches). Superlinear speedup is possible for matrix multiplication algorithm executed in a shared memory multiprocessor due to the existence of a superlinear region. It is a region where cache requirements for matrix storage of the sequential execution incur more cache misses than in parallel execution. This paper shows theoretically and experimentally that there is a region, where the superlinear speedup can be achieved. We provide a theoretical proof of existence of a superlinear speedup and determine boundaries of the region where it can be achieved. The experiments confirm our theoretical results. Therefore, these results will have impact on future software development and exploitation of parallel hardware on the basis of a shared memory multiprocessor architecture. Copyright © 2013 John Wiley & Sons, Ltd.